Autoethnography as feminist method: Sensiting the feminist 'I' - Ettorre, Elizabeth (Routledge, 2018)
Autoethnography is an ideal method to study the ‘feminist I’. Through personal stories, the author reflects on how feminists negotiate agency and the effect this has on one's political sensibilities. Speaking about oneself transforms into stories of political responsibility - a key issue for feminists who function as cultural mediators.
Keywords: approches et analyses; corps; ethnographie; méthodologie; outils; ouvrages de références; point de vue situé; santé; thématiques